Alces americanus subsp. cameloides Milne-Edwards 1867 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Alces americanus subsp. cameloides Milne-Edwards 1867 Synonyms: Alces americanus subsp. bedfordiae Lydekker 1902. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Artiodactyla, pp. 637-722 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 653, DOI: 10.5281/zenodo.7316519